Pleomorphic liposarcoma of bone: a rare primary malignant bone tumour - Tiemeier, GL; Brown, JM; Pratap, SE; McCarthy, C; Kastrenopoulou, A; Bradley, K; Wilson, S; Orosz, Z; Gibbons, CLMH; Oppermann, U; Athanasou, NA (BioMed Central, 2018)
Background Liposarcoma is an extremely rare primary bone sarcoma. Case presentation We report a case of primary pleomorphic liposarcoma that arose in an 18 year old male in the metaphysis of the left tibia. Plain radiographs showed a partly sclerotic lesion and MR imaging a heterogeneous tumour predominantly isointense on T1- and high-signal on T2-weighted sequences with focal areas of increased T1 signal that suppressed with fat saturation. PET/CT showed marked FDG uptake (SUV = 17.1) in the primary tumour as well as a metastasis in the right distal femur and multiple small pulmonary metastases. Histologically, the tumour was a pleomorphic liposarcoma containing large tumour cells with vacuolated cytoplasm and hyperchromatic pleomorphic nuclei as well as numerous lipoblasts and scattered brown fat-like cells. Tumour cells strongly expressed FABP4/aP2, a marker of adipocyte differentiation, and UCP1, a marker of brown fat, but not S100. The case was treated with neoadjuvant MAP chemotherapy, resulting in extensive (> 95%) necrosis in the primary tumour and almost complete resolution of the femoral and pulmonary metastases. Conclusions Pleomorphic liposarcoma can present as a sclerotic primary malignant bone tumour; markers of adipose differentiation are useful in histological diagnosis and neoadjuvant MAP chemotherapy results in significant tumor necrosis.